Bioprosthetic xenopericardium preserved with di- and penta-epoxy compounds: molecular cross-linking mechanisms, surface features and mechanical properties - I. Yu. Zhuravleva; E. V. Karpova; L. A. Oparina; N. Kabos; A. L. Ksenofontov; A. S. Zhuravleva; N. R. Nichay; A. V. Bogachev-Prokophiev; B. A. Trofimov; A. M. Karaskov (Патология кровообращения и кардиохирургия, 2018)
Background. Heart valve bioprostheses made from glutaraldehyde-treated bovine and porcine pericardia are widely used in open and transcatheter valve surgeries. However, the glutaraldehyde cross-linkage leads to bioprosthetic calcification in many patients. Epoxides are advantageous alternatives to glutaraldehyde, since they engender the biomaterial with better calcification resistance. The cross-linking features of an epoxy compound depend on its chemical structure and have not been fully studied so far. Aim. The study is aimed at comparing the effectiveness and molecular mechanisms of biomaterial treatment using diepoxide vs pentaepoxide compounds. Methods. We studied the stability of diepoxide and pentaepoxide in water and aqueous buffered solutions, as well as the amino acid composition, type of epoxide links with collagen matrix (infrared spectroscopy) and mechanical properties of bovine and porcine pericardia treated with 5% diepoxide, a mixture of 2% diepoxide and 1% pentaepoxide, and with alternating 5% diepoxide and 2% pentaepoxide treatments. Results. Diepoxide and pentaepoxide are both stable in aqueous buffer solutions (pH 7.4). Diepoxide provides high linkage density in bovine and porcine pericardia due to reactions with the amino groups of the OHLys, Lys, His, and Arg residues, and the hydroxyl groups of OHPro, Ser, and Tyr, while pentaepoxide reacts only with Met. Pentaepoxide enhances the strength and elasticity of the xenopericardium. Specimens consecutively treated with diepoxide and pentaepoxide were significantly thinner and featured the highest maximal tensile stress, maximal strain and elastic modulus in comparison with tissues treated with 5% diepoxide and diepoxide-pentaepoxide mixture. Conclusion. The alternating diepoxide-pentaepoxide combination for biomaterial cross-linking is a promising trend for bioprosthetic pericardium treatment.